2013
DOI: 10.1007/s10995-013-1341-7
|View full text |Cite
|
Sign up to set email alerts
|

Provider Adherence to Recommended Prenatal Care Content: Does It Differ for Obese Women?

Abstract: Objective To examine provider adherence to prenatal care (PNC) content in obese and non-obese women and perinatal outcomes in obese women experiencing low and medium versus high adherence to PNC content. Methods Provider adherence to PNC content (low <50%, medium 50–79%, and high ≥80%) was compared between obese (n=69) and non-obese (n=128) women in a linked database of deliveries to low-income, minority women from 2003-2004. Sample content items included procedures delivered at every visit (blood pressure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…While early screening for obesity is still an incomplete clinical accomplishment [5], obesity itself has had an impact on our nation's health and our social perceptions of acceptability. It has been reported that obstetrical providers may not adhere uniformly to the monitoring of gestational weight gaining and other variables when treating obese and non-obese pregnant women [6]. Many women have expressed their desire for the conversation to focus on the medical issues brought upon during preconception counseling or while they are pregnant [7].…”
Section: Introductionmentioning
confidence: 99%
“…While early screening for obesity is still an incomplete clinical accomplishment [5], obesity itself has had an impact on our nation's health and our social perceptions of acceptability. It has been reported that obstetrical providers may not adhere uniformly to the monitoring of gestational weight gaining and other variables when treating obese and non-obese pregnant women [6]. Many women have expressed their desire for the conversation to focus on the medical issues brought upon during preconception counseling or while they are pregnant [7].…”
Section: Introductionmentioning
confidence: 99%